Pengaruh Aromaterapi Lavender Terhadap Derajat Insomnia Pada Remaja Putri di SMAN 1 Godean: The Effect of Lavender Aromatherapy on The Degree of Insomnia In Young Girls at SMAN 1 Godean - Julia, Giani Tresna; Shanti, Elvika Fit Ari (LPPM STIKES Guna Bangsa, 2025)
Insomnia is a situation when a person is unable to get adequate sleep, both in quantity and quality, with only short sleep situations, or difficulty sleeping. Sustained insomnia in adolescents can lead to a worsening quality of life and an increased risk of somatic, interpersonal, and psychiatric problems. Lavender aromatherapy can be used to reduce insomnia. Lavender contains linalool which has a calming effect and can induce a person to sleep. This research aims to determine the effect of lavender aromatherapy on the degree of insomnia in the young girls at SMAN 1 Godean. This research is a quasy-experiment with non equivalent control group design. The sample technique was purposive sampling with a total of 34 respondents divided into the experimental group and the control group of 17 respondents. The research instrument used KSPBJ-IRS and observation sheet. Statistical analysis using Wilcoxon test and Mann Whitney U test. The results of the Wilcoxon test in the experimental group obtained a p-value of 0.002 (<0.05) and control group obtained a p-value of 1,000 (>0,05). The results of the Mann Whitney U test obtained a p-value of 0.002 (<0.05). The conclusion is that there is an effect of lavender aromatherapy on the degree of insomnia in young girls at SMAN 1 Godean.